Interactive mobile media search engine - Tay, Jun Bao. (2013)
The proliferation of mobile devices with high-resolution built-in camera has led to a new form of information searching: the input of search engine is no longer restricted to text only, but extended into the form of image and voice as well. In particular, mobile visual search has been widely studied by researchers to develop the new kind of search engine that is adaptable to image-based input. Different approaches have been proposed to optimize the process of feature matching and geometric verification (GV) of images so that the retrieval result is accurate and efficient.